Islamisasi Masyarakat Tanah Jawa Lewat Kultur Kebudayaan Reog Ponorogo Di Jawa Timur, Indonesia - Fadillah Sauma Ramadani; Muhammad Davin Dwi P; Tarish Auliasari Narulita (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The art of Reog Ponorogo is one that has quite long values and history in the process of Islamization of the people of the land of Java, particularly in East Java. This is particularly true for East Java. In Islamizing people in East Java, the values contained in Reog Ponorogo include traditional, religious, cultural, social, political, and historical values. These values are all interrelated in some way. Since Islam was introduced to Java, the traditional art of Reog has been transformed into a form of propaganda that is utilized to disseminate Islamic principles. The purpose of this study is to shed light on the ways in which Reog is utilized as a tool for Islamization in Java. There are a number of symbols connected to the religion of Islam that can be found in Reog. One example of this is the depiction of a horse, which represents the Mi'raj Isra journey that the Prophet Muhammad undertook. Ulrich Beck's theory of the risk society faces is utilized in the method of analysis. Ulrich Beck investigates the ways in which contemporary dangers mold and transform society, as well as the difficulties inherent in mitigating these dangers in a way that is both equitable and environmentally responsible. In the context of the Islamization of Reog culture, through the lens of Ulrich Beck's point of view, it is possible to interpret that the culture of Reog Ponorogo is the result of a modernization process and also a response to increasingly complex changes in both the global and local contexts.